2019
DOI: 10.12678/1089-313x.23.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Readiness for En Pointe Work in Young Ballet Dancers Are There Proven Screening Tools and Training Protocols for a Population at Increased Risk of Injury?

Abstract: To progress to a high level in classical ballet, en pointe is a requirement. The aim of this literature review was to evaluate the available evidence relating to readiness for dancing en pointe, including injury rates in the adolescent dancer population, screening tools, and pre-pointe training methods. It has been emphasized that young dancers are a demographic at increased risk of injury, especially as they progress through the growth spurt and increase their training hours. Dancers are commonly screened at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Therefore, it may be hypothesized that these differences are attributed to the dancer's training effect, since classical dancers adopt the en pointe position more than their contemporary counterparts. This en pointe position is highly challenging for balance, strength, and endurance, which may explain this difference between groups [35].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be hypothesized that these differences are attributed to the dancer's training effect, since classical dancers adopt the en pointe position more than their contemporary counterparts. This en pointe position is highly challenging for balance, strength, and endurance, which may explain this difference between groups [35].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the significant number of ankle injuries in dancers in general, there is a need for improved prepointe screening and en pointe training protocols, as this often represents the crucial timepoint for developing techniques that minimize a dancer's risk of an eventual injury. 2 As such, preventative measures can be taken in cases of PAIS that result from chronic compensation behavior for poor mechanics. After determination for pointe readiness has been made, subsequent evaluation for proper footwear is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, dancers begin pointe training around 12 years of age, 1,2,6,8,12,[15][16][17] which is around the time that the pubertal growth spurts occurs. 1,8,18 However, chronological age does not always equate to bone age.…”
Section: Age Growth and Injurymentioning
confidence: 99%
“…2,6,11 Anatomically, dancers should encompass an array of physical attributes to perform en pointe correctly and safely. 1,2 Dancers are required to demonstrate adequate and stable ankle ROM 1,6,7 (plantar flexing the foot in parallel with the tibia), strong tendu (extending the foot of the working leg across the floor to pointe while the other foot supports weight), adequate strength and alignment in the core and lower extremities, 12,13 and 90° to 100° of plantar flexion at the ankle during relevé. 1,2,4,14 Subsequently, it has been suggested that dancers require at least 2 years of ballet experience prior to going en pointe, 12,13 and pointe training should be discouraged for dancers who are only doing one ballet class a week or have reduced ROM of the ankles and feet.…”
Section: Introductionmentioning
confidence: 99%